Indicators of Growth and Development in the Second Field of Stock and Variety Root Stock Nursery - Erkinovich, Botirov Alisher; Yakhshibekovich, Islamov Sohib (American Journal of Biodiversity, 2025)
This article presents the results of an experiment conducted to study the growth indicators of the 2nd field of the nursery with a deep scientific analysis.